Analysis of Bawaslu's Responsibility in Violations of the Neutrality of the State Civil Apparatus that Result in Losses to Voters in the 2024 Election - Marbun, Enjelika; Sinaga, Budiman (Manunggal Halim Jaya, 2025)
The 2024 elections in Indonesia face various challenges, including violations of election neutrality committed by the State Civil Apparatus (ASN). This violation not only damages the integrity of the election but also has the potential to cause harm to voters. This study aims to analyze Bawaslu's obligations related to these violations and the impact on voters who feel disadvantaged. The research method used is normative juridical analysis with data analysis obtained from relevant legal regulations, official documents, and previous studies. The results showed that violations of ASN neutrality significantly impacted people's voting rights, and many voters felt pressured or disadvantaged by these actions. The research also identified that Bawaslu is legally responsible for addressing these violations and compensating the aggrieved parties. The implications of these findings point to the importance of implementing strict sanctions for violators to ensure fairness in the electoral process and the protection of voters' rights. In conclusion, there is a need to strengthen regulations and education for ASNs to prevent the recurrence of violations in the future.